2007 IEEE Particle Accelerator Conference (PAC) 2007
DOI: 10.1109/pac.2007.4440849
|View full text |Cite
|
Sign up to set email alerts
|

Injection studies on the isis synchrotron

Abstract: The ISIS Facility at the Rutherford Appleton Laboratory in the UK produces intense neutron and muon beams for condensed matter research. It is based on a 50 Hz proton synchrotron which, once the commissioning of a new dual harmonic RF system is complete, will accelerate about 3.5x10 13 protons per pulse from 70 to 800 MeV, corresponding to mean beam powers of 0.2 MW. The multi-turn charge-exchange injection process strongly affects transverse beam distributions, space charge forces, beam loss and therefore ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Those magnets traverse a painting orbit during injection [14]. A painting injection method is an ordinary way to reduce the space charge effect in a synchrotron [15][16][17][18]. The voltage of the power supply was increased by about twice according to increment of the Linac acceleration energy.…”
Section: Rcsmentioning
confidence: 99%
“…Those magnets traverse a painting orbit during injection [14]. A painting injection method is an ordinary way to reduce the space charge effect in a synchrotron [15][16][17][18]. The voltage of the power supply was increased by about twice according to increment of the Linac acceleration energy.…”
Section: Rcsmentioning
confidence: 99%
“…Since the ISIS synchrotron is one of the few machines worldwide where some of these important loss mechanisms can be studied experimentally, a series of theoretical and experimental work programmes has been launched. In particular, and summarised as contributions to this conference, studies on optimising injection [18] and of space charge loss mechanisms [19] are being carried out.…”
Section: Ring Randdmentioning
confidence: 99%
“…Simulations will next look at longitudinal effects. Related studies on ISIS injection are reported in [7].…”
Section: Future and Related Workmentioning
confidence: 99%